Odpowiedzi

Najlepsza Odpowiedź!
2010-01-13T18:47:33+01:00
A) 2a + (3a - 7)=2a+3a-7=5a-7
b)x- (2x-3)=x-2x+3=-x+3
c)3x - (y - 2x)=3x-y+2x=5x-y
d) -(3a + 6) - 4=-3a-6-4=-3a-10
e) -(2x - 1)-(3x+1)=-2x+1-3x-1=-5x
f) (4a - 7b) - (2a + 3b)=4a-7b-2a-3b=2a-10b
g) (2p - r) + (2r - p)=2p-r+2r-p=3p+r
h) (x + y) + (x-z) +(z-y)=x+y+x-z+z-y=2x
Assa ;)
2010-01-13T18:55:10+01:00
A.) 2a+(3a-7)=2a+3a-7=5a-7
b). x-(2x-3)=x-2x+3=x+3
c). 3x-(y-2x)=3x-y+2x=5x-y
d).-3a+6)-4=-3a+6-4=-3a+2
e).-(2x-1)-(3x+1)=-2x+1-3x-1=-5x
f).(4a-7b)-(2a+3b)=4a-7b-2a-3b=2a-10b
g).(2p-r)+(2r-p)=2p-r+2r-p=p+r
h).(x+y)+(x-z)+(z-y)=x+y+x-z+z-y=2x

powinno byc dobrze[;[;